The embryonic origins and genetic programming of emerging haematopoietic stem cells - Ciau-Uitz, A; Patient, R (John Wiley & Sons Ltd, 2016)
Haematopoietic stem cells (HSCs) emerge from the haemogenic endothelium (HE) localised in the ventral wall of the embryonic dorsal aorta (DA). The HE generates HSCs through a process known as the endothelial to haematopoietic transition (EHT), which has been visualised in live embryos and is currently under intense study. However, EHT is the culmination of multiple programming events, which are as yet poorly understood, that take place before the specification of HE. A number of haematopoietic precursor cells have been described before the emergence of definitive HSCs, but only one haematovascular progenitor, the definitive haemangioblast (DH), gives rise to the DA, HE and HSCs. DHs emerge in the lateral plate mesoderm (LPM) and have a distinct origin and genetic programme compared to other, previously described haematovascular progenitors. Although DHs have so far only been established in Xenopus embryos, evidence for their existence in the LPM of mouse and chicken embryos is discussed here. We also review the current knowledge of the origins, lineage relationships, genetic programming, and differentiation of the DHs that leads to the generation of HSCs. Importantly, we discuss the significance of the gene regulatory network (GRN) that controls the programming of DHs, a better understanding of which may aid in the establishment of protocols for the de novo generation of HSCs in vitro. This article is protected by copyright. All rights reserved.